An experimental study of the performance, combustion and emission characteristics of a CI engine under dual fuel mode using CNG and oxygenated pilot fuel blends. (15th June 2015) - Paul, Abhishek; Panua, Raj Sekhar; Debroy, Durbadal; Bose, Probir Kumar
Abstract: During the past few decades, many researchers have proposed a partial replacement of Diesel in the CI engine by substituting it with natural gas in order to reduce the exhaust emission without altering the performance characteristics of the engine too much. Most of these researches have focused on the combustion of natural gas in a dual fuel mode by using Diesel as the pilot fuel. However, the dual fuel operation of natural gas with pilot Diesel reduces the brake thermal efficiency and increases the hydrocarbon emission. The present experimental work explores the potential of using CNG under dual fuel operation by utilizing two different blends of Diesel–ethanol–biodiesel as the pilot fuel. The present study reveals that the increased percentages of ethanol and biodiesel in the pilot fuel triggers an increase in the brake thermal efficiency of the engine. In this study, the NOx emission was also found to decrease with a corresponding increase in the percentages of ethanol and biodiesel in the pilot fuel. The study reveals definite encouraging aspects of using the D45E15B40 and D30E20B50 blends as the pilot fuel because it can extend the range of usage of the CNG to 9000 μs of injection duration. Highlights: A diesel engine is partially modified to allow indirect injection of CNG. The pilot fuel is modified with ethanol and biodiesel inclusion. Increase in ethanol content improves brake thermal efficiency under dual fuel mode. Hydrocarbon emission under dual fuel mode is reduced with increase in ethanol content.